Influence of mouth rinses on the surface hardness of dental resin nano-composite - Khan, Aftab Ahmed (Pak J Med Sci, 2015)
OBJECTIVE: The aim of this research was to assess the effect of mouth rinses with and without alcohol on the hardness of dental nano-filled composite. METHODS: The micro-hardness of fifty circular disk shaped specimens of 7 mm x 2 mm were measured after 14 days. Specimens were immersed into alcohol containing (Listerine and Colgate Perioguard) and alcohol-free (Prodent and Sensodyne Oral antiseptic) mouth rinse solutions. Artificial saliva served as the control. Vickers Micro-hardness was measured with a 30gram load for 30 seconds dwell time by using a diamond indenter. Significant differences were represented by p<0.05, whereas highly significant difference represented by p<0.01. The level of significance (p) was calculated with the help of repeated measure ANOVA. For multiple comparisons, Tukey’s multiple comparison test was used. RESULTS: Statistical analysis revealed highly significant difference between specimens immersed in artificial saliva (control) and Listerine (p<0.01). Whereas significant difference were observed between control and Colgate Periogard (p<0.05). However, no significant difference was observed on comparing Prodent and Sensodyne Oral antiseptic mouth rinses with control group(p>0.05). Control specimens depicted highest value of micro-hardness(60.5746 ± 3.2703) compared to the lowest value seen in specimens immersed in Listerine solvent(54.4687 ± 1.0937). CONCLUSION: Alcohol containing mouth rinsing solutions have more deleterious effect on hardness of nano composites as compared to alcohol-free mouth rinses.